Animal diversity - Hickman, Cleveland P.; Roberts, Larry S.; Larson, Allan ([S.l.] : Mcgraw-Hill College, 1999)
This text, suitable for zoology or related courses assumes students have previous knowledge in general biology, genetics and/or chemistry. It has an emphasis on animal diversity with an introduction to evolution and classification.
Keywords: animal diversity